Sharing the words of wisdom / Suzaina Ismail - Ismail, Suzaina (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
Engagement session with people from the industry was organized by the Division of Research, Industrial Linkages, Community and Alumni Networking of UiTM Perak Branch. This programme aimed to share information and strengthen the collabora-tive relationship between UiTM Perak Branch and the related industries. It was also intended to improve the teaching and learning process at the university in order to produce holistic graduates, thus meeting the current market needs. The two main highlights of the programme were a forum titled “Graduate Employability Towards Industry Revolution 4.0” and a memorandum of understanding (MoU) signing session. The programme was participated by 12 speakers from various industries that are relat-ed to the courses offered by the university. This programme was also at-tended by 274 lecturers, as well as 237 final year undergraduate students from various programmes from both Seri Iskandar and Tapah campuses.